Changing Trends of Suicide in Punjab from the Year 2016 to 2020: A Comparative Study - Aftab Asif; Sumaira Ayub; Irum Aamer; Usama Ali Cheema (Journal of Liaquat National Hospital)
Background: Each year, around 800,000 people die by suicide. The world is facing multiple issues related to economic recession and disastrous health conditions. In turn, people must face a high rise in poverty, unemployment, financial crises, and domestic and family issues which are ultimately linked with serious mental health problems. Objective: The study aimed to get a deeper insight into the prevalence and changing trends of suicide in Pakistan from the year 2016 to 2020. Methods: This study followed a descriptive approach. The data was collected considering two regionally published newspaper archives. The suicide cases reported from January 2016 to December 2020 were considered only. The data based on age, gender, locality, year, marital status, methods adopted, and reasons to commit suicide were extracted. Results: A total of 2411 suicide cases were reported in the newspaper based on medico-legal police reports, during those five years. Most of the suicide victims were male with 1434 (59.5%) cases, while 977 (40.5%) were females. The age range was from 10 to 80 years (mean=28.12, SD=10.96). The young adults (19 to 39 years) cases were reported highest, 932 (38.7%), and 238 (9.9%) suicide victims were adolescents (18 years and below). About 47.9% (1153) of suicide victims were married. The most adopted methods for committing suicide were chemical poisoning, strangulation, gunshot, and drowning. Family discord/disputes, failed love affairs, domestic violence, and financial crises including poverty and unemployment were reported as contributing factors to suicide. Further, year-wise differences were also discussed. Conclusion: The study demonstrates the rise in suicide cases in Pakistan, highlighting the contributing factors that facilitate such a rise. So, with the help of this study, intervention strategies could be devised to deal with the risk factors to control suicide cases in Pakistan.